Possible presentation of Kernohan–Woltman notch phenomenon in a young female with heavy drinking: a case report - Kapil Chauhan; Jabari-Ture Brooks; Mosunmola Oyawusi; Roger Weir (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background A subdural hematoma is a type of traumatic brain injury that results from the rupture of the bridging veins. It often presents with various neurological deficits. The Kernohan–Woltman notch phenomenon (KWNP) is a rare complication associated with subdural hematomas, characterized by ipsilateral hemiparesis due to compression of the contralateral cerebral peduncle. Case presentation We present a case of a 30-year-old female with a left subdural hematoma who exhibited paradoxical ipsilateral hemiparesis and discuss the appearance of KWNP in the context of alcohol withdrawal. We also report on the appearance of delirium tremens 6 days after evacuation. Conclusion In our report, we effectively rule out other causes of ipsilateral hemiparesis such as cerebrovascular accident or mass effect, and demonstrate a rare presentation of KWNP in an uncommon demographic. Our report also demonstrates an incidental finding of delirium tremens that may have been delayed in presentation due to intubation. The findings contribute to further research on these uncommon neurological and psychiatric manifestations.